Simultaneous deactivation of FAK and Src improves the pathology of hypertrophic scar - Su, Linlin (Sci Rep, 2016)
Hypertrophic scar (HS) is a serious fibrotic skin condition with currently no satisfactory therapy due to undefined molecular mechanism. FAK and Src are two important non-receptor tyrosine kinases that have been indicated in HS pathogenesis. Here we found both FAK and Src were activated in HS vs. normal skin (NS), NS fibroblasts treated with TGF-β1 also exhibited FAK/Src activation. Co-immunoprecipitation and dual-labelled immunofluorescence revealed an enhanced FAK-Src association and co-localization in HS vs. NS. To examine effects of FAK/Src activation and their interplay on HS pathogenesis, site-directed mutagenesis followed by gene overexpression was conducted. Results showed only simultaneous overexpression of non-phosphorylatable mutant FAK Y407F and phosphomimetic mutant Src Y529E remarkably down-regulated the expression of Col I, Col III and α-SMA in cultured HS fibroblasts, alleviated extracellular matrix deposition and made collagen fibers more orderly in HS tissue vs. the effect from single transfection with wild-type or mutational FAK/Src. Glabridin, a chemical found to block FAK-Src complex formation in cancers, exhibited therapeutic effects on HS pathology probably through co-deactivation of FAK/Src which further resulted in FAK-Src de-association. This study suggests FAK-Src complex could serve as a potential molecular target, and FAK/Src double deactivation might be a novel strategy for HS therapy.